Assembling nostalgia: devices for affective captation on the re:heritage market. Issue 6 (3rd July 2017) - Brembeck, Helene; Sörum, Niklas
Abstract: This article builds on the current rethinking of nostalgia in heritage studies and an increasing amount of research that explores the formatting of customer – producer relationships in terms of 'market attachments' to analyse how nostalgia is performative on the market for retro, vintage and second hand, what we call the re:heritage market. Based on a multi-sited study including offline and online ethnographic observations, photography and qualitative interviews with shop owners and staff at a selection of central streets in Gothenburg, Sweden, the article explores the way shop owners work with nostalgia in order to attract, or 'captate', the public, through engaging affective market devices. Our particular contribution is to show how the re:heritage market contribute to our understanding of an alternative of cultural heritage, through configuring exchange and value, and details how 'affective captation' adds conceptual strength for understanding the emotive and sensate pull of certain market-based heritage practices. Staging nostalgic encounters involves practices of selecting, collecting, displaying and preserving for the future: practices that are vital for all heritage-making. A variety of actors are involved in this unconventional of heritage at safe a distance from traditional heritage practices.